Laminate

The laminate, featuring a resin substrate, low refractive index layer, and pressure-sensitive adhesive layer with specific modulus and thickness ranges, addresses adhesion issues in high humidity environments, ensuring reliable attachment and moisture resistance for optical products.

JP2025059267APending Publication Date: 2025-04-10NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023169246
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing laminates used in optical products with light guide plates tend to peel off in high humidity environments, leading to adhesion issues and potential wavy glue formation.

Method used

A laminate comprising a resin substrate, a low refractive index layer with a refractive index of 1.30 or less, and a pressure-sensitive adhesive layer, where the adhesive layer's shear storage modulus at 60° C. is within the range of 2000 Pa/μm to 15000 Pa/μm, ensuring excellent adhesion in high humidity.

Benefits of technology

The laminate achieves excellent adhesion to objects in high humidity environments, preventing peeling and wavy glue formation, while maintaining moisture resistance and transparency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059267000001_ABST
    Figure 2025059267000001_ABST
Patent Text Reader

Abstract

To provide a laminate which is excellent in adhesion to an object to be stuck under high humidity environment.SOLUTION: A laminate includes a resin base material, a low refractive index layer, and an adhesive layer. The low refractive index layer is arranged on one side of the resin base material. A refractive index of the low refractive index layer is 1.30 or less. The adhesive layer is arranged on a side opposite to the low refractive index layer with respect to the resin base material. When a shear storage elastic modulus at 60°C of the adhesive layer is represented by G', and thickness of the adhesive layer is represented by t, the laminate satisfies the following expression (1): 2,000[Pa / μm]≤G' / t≤15,000[Pa / μm].SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate. [Background technology]

[0002] It is known that a laminate including a low refractive index layer having a refractive index smaller than that of the light guide plate is attached to a light guide plate that propagates light, thereby arbitrarily controlling the propagation of light in the light guide plate. As such a laminate, for example, a laminate including a base material and a variable refractive index extraction layer provided on the base material, the variable refractive index extraction layer including a first region in which a first material having a relatively small refractive index is selectively printed, and a second region in which a second material having a relatively large refractive index is overcoated on the first material, has been proposed (see, for example, Patent Document 1). In the laminate described in Patent Document 1, an adhesive layer is formed on the surface of the base material opposite to the variable refractive index extraction layer, and the laminate is attached to the light guide plate by the adhesive layer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2014 / 031726 Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, the applications of optical products including light guide plates have become more diverse, and the optical products may be exposed to high-humidity environments. In this case, if the laminate described in Patent Document 1 is applied to an optical product that may be exposed to a high-humidity environment, the laminate may peel off from the light guide plate. The present invention has been made to solve the above-mentioned problems in the conventional art, and a main object of the present invention is to provide a laminate that has excellent adhesion to an object to be stuck in a high humidity environment. [Means for solving the problem]

[0005] [1] A laminate according to an embodiment of the present invention includes a resin substrate, a low refractive index layer, and a pressure-sensitive adhesive layer. The low refractive index layer is disposed on one side of the resin substrate. The low refractive index layer has a refractive index of 1.30 or less. The pressure-sensitive adhesive layer is disposed on the opposite side of the resin substrate to the low refractive index layer. The laminate satisfies the following formula (1), where G' is the shear storage modulus of the pressure-sensitive adhesive layer at 60°C and t is the thickness of the pressure-sensitive adhesive layer. 2000[Pa / μm]≦G´ / t≦15000[Pa / μm]···(1) [2] In the laminate described in the above [1], the pressure-sensitive adhesive layer may have a thickness t exceeding 5 μm and less than 50 μm. [3] In the laminate according to the above [1] or [2], the pressure-sensitive adhesive layer may have a shear storage modulus G' at 60°C of 80,000 Pa or more. Effect of the Invention

[0006] According to an embodiment of the present invention, a laminate having excellent adhesion to an object to be attached even in a high humidity environment can be provided. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is a schematic cross-sectional view of a laminate according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of an optical article comprising the stack of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to these embodiments. Note that, in order to make the drawings easy to see and understand, the drawings are drawn typically or conceptually, and the length, width, shape, size, ratio, direction, number, etc. may differ from the actual ones, and there may be no correspondence between the drawings.

[0009] A. Overall structure of the laminate FIG. 1 is a schematic cross-sectional view of a laminate according to one embodiment of the present invention. The laminate 100 in the illustrated example includes a resin substrate 1, a low refractive index layer 2, and a pressure-sensitive adhesive layer 3. The low refractive index layer 2 is disposed on one side of the resin substrate 1. The refractive index of the low refractive index layer 2 is 1.30 or less. The pressure-sensitive adhesive layer 3 is disposed on the opposite side of the resin substrate 1 to the low refractive index layer 2. The laminate 100 satisfies the following formula (1), where G' is the shear storage modulus of the pressure-sensitive adhesive layer 3 at 60°C and t is the thickness of the pressure-sensitive adhesive layer 3. 2000[Pa / μm]≦G´ / t≦15000[Pa / μm]···(1) According to this configuration, since the laminate satisfies the above formula (1), the adhesion to the object to be affixed can be improved in a high humidity environment (typically 80% RH (relative humidity) or higher). Therefore, even if the laminate having the low refractive index layer is attached to the object to be affixed by the adhesive layer and exposed to a high temperature environment, the laminate can be prevented from peeling off from the object to be affixed, and the laminate can be prevented from waviness caused by the adhesive layer (hereinafter, referred to as adhesive waviness). In other words, the moisture resistance of the laminate can be significantly improved.

[0010] The shear storage modulus G' (hereinafter referred to as G' / t) of the pressure-sensitive adhesive layer 3 at 60°C relative to the thickness t of the pressure-sensitive adhesive layer 3 is preferably 2500 Pa / μm or more, more preferably 3000 Pa / μm or more, and even more preferably 5000 Pa / μm or more. On the other hand, G' / t is, for example, 14000 Pa / μm or less, preferably 13000 Pa / μm or less, more preferably 12000 Pa / μm or less, and even more preferably 8000 Pa / μm or less. When G' / t is in this range, the moisture resistance of the laminate can be stably improved.

[0011] The thickness t of the pressure-sensitive adhesive layer 3 exceeds 5 μm, and is preferably 8 μm or more, more preferably 10 μm or more, and even more preferably 12 μm or more. On the other hand, the thickness t of the pressure-sensitive adhesive layer 3 is, for example, less than 50 μm, and preferably 45 μm or less, more preferably 30 μm or less, and even more preferably 23 μm or less. When the thickness of the pressure-sensitive adhesive layer is within this range, the laminate can stably satisfy the above formula (1).

[0012] The shear storage modulus G' of the pressure-sensitive adhesive layer 3 at 60°C is, for example, 70,000 Pa or more, preferably 80,000 Pa or more, more preferably 85,000 Pa or more, and even more preferably 95,000 Pa or more. Meanwhile, the shear storage modulus G' of the pressure-sensitive adhesive layer at 60°C is, for example, 130,000 Pa or less, preferably 120,000 Pa or less. The shear storage modulus G' of the pressure-sensitive adhesive layer at 60°C can be determined, for example, in accordance with the method described in JIS K7244-1 "Plastics - Test method for dynamic mechanical properties", by reading the value at 60°C when measured at a temperature rise rate of 5°C / min in the range of -50°C to 150°C under a frequency condition of 1Hz. When the shear storage modulus of the pressure-sensitive adhesive layer is within this range, the laminate can more stably satisfy the above formula (1).

[0013] The shear storage modulus G' of the pressure-sensitive adhesive layer 3 at 23° C. is, for example, 90,000 Pa to 200,000 Pa, and preferably 100,000 Pa to 190,000 Pa. The shear storage modulus G' of the pressure-sensitive adhesive layer at 23° C. can be determined, for example, in accordance with the method described in JIS K 7244-1 "Plastics - Test methods for dynamic mechanical properties", by reading the value at 23° C. when measured at a temperature rise rate of 5° C. / min in the range of -50° C. to 150° C. under conditions of a frequency of 1 Hz.

[0014] The resin substrate, the low refractive index layer, and the pressure-sensitive adhesive layer will be specifically described below.

[0015] B.Resin base material The resin substrate 1 is typically capable of transmitting light. The total light transmittance of the resin substrate 1 is, for example, 70% to 100%, and preferably 80% to 99%. When the total light transmittance of the resin substrate is in such a range, the laminate as a whole can achieve excellent transparency. Therefore, adverse effects in the application of the laminate can be suppressed. The total light transmittance is measured, for example, by any appropriate haze meter.

[0016] Any appropriate configuration may be adopted for the resin substrate 1. Examples of the material for the resin substrate 1 include a thermoplastic resin material and a curable resin material, and preferably a thermoplastic resin material.

[0017] Examples of thermoplastic resin materials include (meth)acrylic resins such as polymethyl methacrylate (PMMA); cycloolefin (COP) resins; polyester resins such as polyethylene terephthalate (PET); polyvinyl acetal resins; polycarbonate resins; polyarylate resins; and polyurethane resins. Note that (meth)acrylic refers to acrylic and / or methacrylic. The materials of the resin substrate 1 may be used alone or in combination. Among such materials of the resin substrate 1, (meth)acrylic resins are preferred.

[0018] The resin substrate 1 has a thickness of, for example, 10 μm to 80 μm, and preferably 20 μm to 40 μm.

[0019] C. Low refractive index layer The low refractive index layer 2 is typically provided directly on the surface of the resin substrate 1 . The refractive index of the low refractive index layer 2 is 1.30 or less as described above, and the lower limit is more than 1.00. The refractive index of the low refractive index layer 2 is preferably 1.13 to 1.28, more preferably 1.14 to 1.27, even more preferably 1.15 to 1.26, and particularly preferably 1.16 to 1.25. The refractive index refers to a refractive index measured at a wavelength of 550 nm unless otherwise specified. The refractive index is, for example, a value measured by the method described in the examples below.

[0020] The total light transmittance of the low refractive index layer 2 is, for example, 85% to 99%, preferably 87% to 98%, and more preferably 89% to 97%. When the total light transmittance of the low refractive index layer is in such a range, excellent transparency can be achieved as a whole laminate.

[0021] The haze of the low refractive index layer 2 is, for example, less than 5%, and preferably less than 3%. On the other hand, the haze is, for example, 0.1% or more, and for example, 0.2% or more. If the haze of the low refractive index layer is in such a range, excellent transparency can be achieved as a whole laminate. The haze can be calculated from the following formula using a value measured with a haze meter (for example, "HM-150" manufactured by Murakami Color Research Laboratory Co., Ltd.). Haze (%) = [Diffuse transmittance (%) / Total light transmittance (%)] x 100 (%)

[0022] The thickness of the low refractive index layer 2 is, for example, 0.3 μm to 10 μm, and preferably 0.5 μm. The thickness of the low refractive index layer is preferably from 0.8 to 1.2 μm. If the thickness of the low refractive index layer is within this range, a laminate having excellent moisture resistance can be made thinner.

[0023] Any appropriate configuration capable of achieving the above-mentioned desired characteristics may be adopted for the low refractive index layer 2. The low refractive index layer 2 may have any appropriate pattern shape depending on the application of the laminate 100.

[0024] Materials constituting the low refractive index layer 2 may be, for example, materials described in International Publication No. 2004 / 113966, JP 2013-254183 A, and JP 2012-189802 A. Representative examples of materials constituting the low refractive index layer include silicon compounds. Examples of silicon compounds include silica-based compounds; hydrolyzable silanes and their partial hydrolysates and dehydration condensates; silicon compounds containing silanol groups; and activated silica obtained by contacting silicate with acid or ion exchange resin. Materials constituting the low refractive index layer include organic polymers; polymerizable monomers (e.g., (meth)acrylic monomers and styrene monomers); and curable resins (e.g., (meth)acrylic resins, fluorine-containing resins, and urethane resins). These materials may be used alone or in combination.

[0025] In one embodiment, the low refractive index layer 2 may contain spaces such as holes and gaps therein. In this case, the porosity of the low refractive index layer 2 is, for example, 20 volume % to 60 volume %, preferably 25 volume % to 55 volume %, more preferably 30 volume % to 50 volume %, and further preferably 35 volume % to 45 volume %. With such a porosity, the refractive index of the low refractive index layer can be set in an appropriate range and strength can be ensured. Here, the porosity is, for example, a value calculated by the Lorentz-Lorenz's formula from the value of the refractive index measured by an ellipsometer.

[0026] The size of the pores that can be contained in the low refractive index layer 2 can be adjusted to a desired size depending on the purpose and use. The size of the pores that can be contained in the low refractive index layer 2 is, for example, 2 nm or more, preferably 5 nm or more, more preferably 10 nm or more, and even more preferably 20 nm or more. On the other hand, the size of the pores that can be contained in the low refractive index layer is, for example, 500 nm or less, preferably 200 nm or less, and more preferably 100 nm or less. The size of the pores refers to the diameter of the major axis of the pores, out of the diameter of the major axis and the diameter of the minor axis.

[0027] The size of the pores can be quantified by the BET test method. In one embodiment, 0.1 g of a measurement sample (for example, the formed low refractive index layer) is placed in the capillary of a specific surface area measurement device (for example, "ASAP2020" manufactured by Micromeritics), and then the measurement sample is dried under reduced pressure for 24 hours at room temperature to remove gas contained in the measurement sample. Then, an adsorption isotherm is drawn by adsorbing nitrogen gas to the measurement sample, and the pore distribution is obtained. This allows the size of the pores to be evaluated.

[0028] The low refractive index layer having a space therein includes, for example, a low refractive index layer made of a porous body and / or a layer containing an air layer at least in a part thereof. The low refractive index layer typically contains aerogel and / or particles (which may be, for example, hollow fine particles and / or porous particles). The low refractive index layer is preferably a nanoporous layer (specifically, a layer in which the diameter of 90% or more of the pores is 10 -1 nm~10 3 The layer may be a low refractive index layer in the range of 1 nm.

[0029] Any suitable particle may be used as the particle. The particle is typically composed of a silica-based compound. Examples of particle shapes include spherical, plate-like, needle-like, string-like, and bunch-of-grapes shapes. Examples of string-like particles include particles in which a plurality of particles having a spherical, plate-like, or needle-like shape are linked together in a string-like shape, short fiber-like particles (for example, short fiber-like particles described in JP-A-2001-188104), and combinations thereof. The string-like particles may be linear or branched. Examples of bunch-of-grapes particles include particles in which a plurality of spherical, plate-like, and needle-like particles are aggregated to form a bunch-of-grapes shape. The shape of the particles can be confirmed, for example, by observation using a transmission electron microscope.

[0030] An example of the low refractive index layer 2 is a structure composed of one or more types of structural units that form a fine void structure, and these structural units are bonded together (for example, chemically bonded via catalytic action). Examples of the shape of the structural units include particulate, fibrous, rod-like, and flat-plate-like. The structural units may have only one shape, or may have two or more shapes in combination.

[0031] A specific example of the low refractive index layer 2 is a low refractive index layer composed of a porous body in which particles having micropores (hereinafter referred to as micropore particles) are chemically bonded to each other. Such a low refractive index layer can be obtained, for example, by chemically bonding micropore particles to each other. The shape of the micropore particles is not particularly limited, and may be, for example, spherical or other shapes. In addition, the micropore particles may be, for example, sol-gel beaded particles, nanoparticles (for example, hollow nanosilica nanoballoon particles), nanofibers, etc. The micropore particles typically include inorganic substances. Specific examples of inorganic substances include silicon (Si), magnesium (Mg), aluminum (Al), titanium (Ti), zinc (Zn), and zirconium (Zr). These may be used alone or in combination. In one embodiment, the micropore particles are, for example, micropore particles of a silicon compound, and the porous body is, for example, a silicone porous body. The micropore particles of a silicon compound include, for example, a pulverized product of a gel-like silica compound.

[0032] Another example of the low refractive index layer 2 is a layer containing a fibrous material such as nanofibers, in which a space is formed by the entanglement of the fibrous material. Further examples of the low refractive index layer include a layer formed using hollow nanoparticles or nanoclay, and a layer formed using hollow nanoballoons or magnesium fluoride. The low refractive index layer may be composed of a single constituent material or a plurality of constituent materials. The low refractive index layer may be composed of a single form of the above examples, or a plurality of forms of the above examples.

[0033] The low refractive index layer 2 may be, for example, an open-cell structure in which the pore structure is continuous. The open-cell structure means that the pore structure is three-dimensionally connected in a porous body (for example, a silicone porous body), and can also be said to be a state in which the spaces of the pore structure are continuous. The open-cell structure of the low refractive index layer can increase the porosity. It is difficult to form an open-cell structure using closed-cell particles having individual pore structures such as hollow particles (for example, hollow silica). However, when silica sol particles (pulverized product of a gel-like silicon compound that forms a sol) are used, for example, the silica sol particles can have a three-dimensional dendritic structure, so that the dendritic particles settle and accumulate in the coating film (coated film of a sol containing a pulverized product of a gel-like silicon compound), and the open-cell structure can be easily formed. The low refractive index layer preferably has a monolith structure in which the open-cell structure includes a plurality of pore distributions. The monolith structure means, for example, a hierarchical structure including a structure in which nano-sized fine pores exist and an open-cell structure in which nano-sized fine pores are aggregated. The monolithic structure, for example, can provide film strength through fine pores while providing high porosity through a coarse open-cell structure, thereby achieving both film strength and high porosity.

[0034] For example, the monolith structure can be formed by controlling the pore distribution of the void structure generated in the gel (gel silicon compound) before pulverizing into silica sol particles. Also, for example, when pulverizing the gel silicon compound, the particle size distribution of the silica sol particles after pulverization can be controlled to a predetermined size, thereby forming a monolith structure. Note that the particle size distribution can be measured by, for example, a particle size distribution evaluation device such as dynamic light scattering method or laser diffraction method, and an electron microscope such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).

[0035] As described above, the low refractive index layer 2 may contain pulverized gel compounds such as gel silicon compounds, and the pulverized particles are chemically bonded to each other. The chemical bond is not particularly limited, and examples thereof include cross-linking, covalent bonding, and hydrogen bonding. The volume average particle diameter of the pulverized particles in the low refractive index layer 2 is, for example, 0.10 μm or more, preferably 0.20 μm or more, and more preferably 0.40 μm or more. On the other hand, the volume average particle diameter of the pulverized particles in the low refractive index layer 2 is, for example, 2.00 μm or less, preferably 1.50 μm or less, and more preferably 1.00 μm or less. The volume average particle diameter is an index of the variation in particle size of the pulverized particles, and is determined, for example, by particle size distribution measurement.

[0036] The low refractive index layer 2 may contain silicon atoms. For example, the silicon atoms contained in the low refractive index layer 2 are preferably siloxane-bonded. Of all silicon atoms contained in the low refractive index layer 2, the proportion of unbonded silicon atoms (specifically, residual silanols) is, for example, less than 50%, preferably 30% or less, and more preferably 15% or less.

[0037] The low refractive index layer 2 can be formed, for example, by coating or printing a low refractive index layer forming liquid (sometimes referred to as a coating liquid) on the surface of the resin substrate 1. More specifically, the low refractive index layer 2 can be formed by heating a coating film or a printed layer of the low refractive index layer forming liquid formed on the resin substrate 1.

[0038] In one embodiment, the coating film can be formed using a coating liquid containing microporous particles, and the microporous particles can be chemically bonded to each other by heating (including drying) this coating liquid. The coating liquid containing microporous particles is, for example, a suspension. For example, a catalyst (crosslinking reaction promoter) that promotes crosslinking between microporous particles (for example, a dehydration condensation reaction of residual silanol groups that may be contained in the microporous particles) and / or a substance (catalyst generator) that generates a catalyst (crosslinking reaction promoter) may be added to the coating liquid. Examples of the catalyst include photoactive catalysts and thermally active catalysts. Examples of the substance (catalyst generator) that generates a catalyst include photocatalyst generators and thermal catalyst generators. Examples of the photocatalyst generator include photobase generators (catalysts that generate a basic catalyst by light irradiation) and photoacid generators (substances that generate an acidic catalyst by light irradiation). For example, the microporous particles are pulverized products of a gel-like compound (preferably, a gel-like silicon compound), and the low refractive index layer is a low refractive index layer composed of a porous body (preferably, a silicone porous body) containing the pulverized product of the gel-like compound. Such microporous particles may have a state in which the three-dimensional structure of the gel-like compound before pulverization is dispersed in the three-dimensional basic structure, and a structure based on the three-dimensional basic structure may be formed by using such microporous particles. Specifically, a new structure different from the three-dimensional structure of the gel-like compound may be formed. In this way, the finally obtained low refractive index layer (low refractive index layer) may have a low refractive index similar to that of an air layer, for example. In addition, by chemically bonding the microporous particles to each other, the above three-dimensional basic structure can be fixed, and sufficient strength can be ensured in the finally obtained low refractive index layer (low refractive index layer). The specific configuration and details of the formation method of the low refractive index layer (low refractive index layer) are described, for example, in International Publication No. 2019 / 151073. The description of the publication is incorporated herein by reference.

[0039] The coating thickness of the coating liquid can be set according to the thickness desired for the low refractive index layer 2. The heating temperature of the coating film (coating liquid) is, for example, 20° C. or higher, and preferably 50° C. or higher. Meanwhile, the heating temperature of the coating film (coating liquid) is, for example, 200° C. or lower, and preferably 150° C. or lower. The heating time of the coating film (coating liquid) is, for example, 10 seconds or longer. Meanwhile, the heating time of the coating film (coating liquid) is, for example, 24 hours or shorter, preferably 1 hour or shorter, more preferably 30 minutes or shorter, and even more preferably 10 minutes or shorter.

[0040] D.Adhesive layer The pressure-sensitive adhesive layer 3 is typically provided directly on the surface of the resin substrate 1 opposite the surface on which the low refractive index layer 2 is provided. The pressure-sensitive adhesive layer 3, which will be described in detail later, is provided to attach the laminate 100 to an object to be attached (typically an optical member). Any appropriate pressure-sensitive adhesive may be used as the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer 3, so long as it has the above-mentioned properties. A typical example of the pressure-sensitive adhesive is an acrylic pressure-sensitive adhesive (acrylic pressure-sensitive adhesive composition).

[0041] The acrylic adhesive composition typically contains a (meth)acrylic polymer as a main component. The (meth)acrylic polymer may be contained in the adhesive composition in a proportion of, for example, 50% by mass or more, preferably 70% by mass or more, and more preferably 90% by mass or more of the solid content of the adhesive composition. The (meth)acrylic polymer contains a structural unit derived from an alkyl (meth)acrylate. The (meth)acrylate includes an acrylate and / or a methacrylate. The content of the structural unit derived from the alkyl (meth)acrylate in the (meth)acrylic polymer is, for example, 80% by mass or more, preferably 90% by mass or more. The alkyl group of the alkyl (meth)acrylate may, for example, be a linear or branched alkyl group having 1 to 18 carbon atoms. The average number of carbon atoms in the alkyl group is preferably 3 to 9, more preferably 3 to 6. The alkyl (meth)acrylate is particularly preferably butyl acrylate.

[0042] The (meth)acrylic polymer may contain, in addition to the constituent units derived from the alkyl (meth)acrylate, a constituent unit derived from a copolymerizable monomer copolymerizable with the alkyl (meth)acrylate. When the (meth)acrylic polymer contains a constituent unit derived from a copolymerizable monomer, the shear storage modulus G' of the pressure-sensitive adhesive layer at 60°C can be stably adjusted to the above range. Examples of the copolymerizable monomer include carboxyl group-containing monomers, hydroxyl group-containing monomers, amide group-containing monomers, aromatic ring-containing (meth)acrylates, heterocycle-containing vinyl monomers, etc. The copolymerizable monomers may be used alone or in combination. Of the copolymerizable monomers, preferred are carboxyl group-containing monomers such as (meth)acrylic acid; hydroxyl group-containing monomers such as 4-hydroxybutyl acrylate; and heterocycle-containing vinyl monomers such as N-acryloylmorpholine. The content of the structural units derived from the copolymerization monomer in the (meth)acrylic polymer is, for example, 0 mass% to 20 mass%, preferably 0.5 mass% to 15 mass%, more preferably 0.8 mass% to 13 mass%, and particularly preferably 5 mass% to 12 mass%.

[0043] The acrylic adhesive composition preferably contains a silane coupling agent and / or a crosslinking agent. Examples of the silane coupling agent include an epoxy group-containing silane coupling agent. Examples of the crosslinking agent include an isocyanate-based crosslinking agent and a peroxide-based crosslinking agent. Furthermore, the acrylic adhesive composition may contain an antioxidant and / or a conductive agent. Details of the adhesive layer or the acrylic adhesive composition are described in, for example, JP 2006-183022 A, JP 2015-199942 A, JP 2018-053114 A, JP 2016-190996 A, and WO 2018 / 008712 A, and the descriptions in these publications are incorporated herein by reference.

[0044] E. Usage of the laminate 2, the laminate 100 described above is typically applicable to an optical product 200 including a light guide plate 10. In one embodiment, the laminate 100 is attached by the pressure-sensitive adhesive layer 3 to the light guide plate 10, which is an example of an object to be attached. The light guide plate 10 can typically propagate light incident from a light source (typically an LED) not shown in the figure in a predetermined direction (the left-right direction in FIG. 2). In the illustrated example, the laminate 100 is attached to the entire light guide plate 10. This allows the light propagating through the light guide plate to be arbitrarily controlled. EXAMPLES

[0045] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring each property are as follows. Unless otherwise specified, "%" and "parts" in the examples are based on mass.

[0046] (1) Refractive index The laminates obtained in the examples and comparative examples were cut into a size of 100 mm x 100 mm to prepare samples. The samples were attached to the surface of a glass plate with an adhesive layer. The thickness of the glass plate was 0.7 mm. The center of the back surface of the glass plate (diameter of about 20 mm) was filled with black marker to prepare a sample that was not reflective on the back surface of the glass plate. The samples were set in an ellipsometer (JA Woollam Japan: VASE) and the refractive index was measured under conditions of a wavelength of 550 nm and an incident angle of 50 to 80 degrees.

[0047] (2) Reliability test in high humidity environment The laminates obtained in the examples and comparative examples were cut into samples of 100 mm x 100 mm in size. The samples were then attached to the surface of a glass plate with an adhesive layer. The glass plate had a size of 100 mm x 100 mm and a thickness of 0.7 mm. Next, the sample attached to the glass plate was left to stand under conditions of 60°C and 95% RH for 6 hours, then cooled to conditions of 30°C and 95% RH at a temperature drop rate of 3.75°C / h, and left to stand under conditions of 30°C and 95% RH for 8 hours. Then, the temperature was raised to conditions of 60°C and 95% RH at a temperature drop rate of 15°C / h. This cycle was repeated 10 times. Then, peeling of the sample from the glass plate was visually observed. This reliability test was performed twice for each sample, and evaluated according to the following criteria. ○: In both reliability tests, the sample did not peel off from the glass plate and no waviness of the adhesive was observed (0 / 2). ×: In at least one of the two reliability tests, the sample peeled off from the glass plate or wavy adhesive was observed (1 / 2 or 2 / 2).

[0048] [Preparation Example 1] Preparation of coating liquid for forming low refractive index layer (1) Gelation of silicon compounds 0.95 g of methyltrimethoxysilane (MTMS), a precursor of a silicon compound, was dissolved in 2.2 g of dimethyl sulfoxide (DMSO) to prepare mixed solution A. 0.5 g of 0.01 mol / L oxalic acid solution was added to this mixed solution A and stirred at room temperature (23°C) for 30 minutes to hydrolyze MTMS, producing mixed solution B containing tris(hydroxy)methylsilane. To 5.5 g of DMSO, 0.38 g of 28% by mass ammonia water and 0.2 g of pure water were added, and then the above mixed solution B was further added and stirred at room temperature (23°C) for 15 minutes to gel tris(hydroxy)methylsilane, thereby obtaining mixed solution C containing a gel-like silicon compound. (2) Aging treatment The mixed solution C containing the gel-like silicon compound prepared as above was incubated as it was at 40° C. for 20 hours for aging treatment. (3) Crushing Next, the gel-like silicon compound aged as described above was crushed into granules of several mm to several cm in size using a spatula. Next, 40 g of isobutyl alcohol (IBA) was added to the mixed liquid C, and after light stirring, the mixture was left to stand at room temperature for 6 hours, and the solvent and catalyst in the gel were decanted. The same decantation process was performed three times to replace the solvent and obtain a mixed liquid D. Next, the gel-like silicon compound in the mixed liquid D was crushed (high-pressure media-less crushing). The crushing process (high-pressure media-less crushing) was performed using a homogenizer (manufactured by SMT Co., Ltd., product name "UH-50"), and 1.85 g of the gel-like compound and 1.15 g of IBA in the mixed liquid D were weighed into a 5 cc screw bottle, and then crushed for 2 minutes under the conditions of 50 W and 20 kHz. The gel-like silicon compound in the mixed solution D was pulverized by this pulverization process, and the mixed solution D became a pulverized sol solution E. The volume average particle diameter, which indicates the particle size variation of the pulverized material contained in the sol solution E, was confirmed to be 0.10 μm to 0.30 μm using a dynamic light scattering nanotrack particle size analyzer (manufactured by Nikkiso Co., Ltd., UPA-EX150 type), and was found to be 0.10 μm to 0.30 μm. Furthermore, 0.062 g of a 1.5 mass % concentration MEK (methyl ethyl ketone) solution of a photobase generator (Wako Pure Chemical Industries, Ltd.: product name WPBG266) and 0.036 g of a 5% concentration MEK solution of bis(trimethoxysilyl)hexane were added to 0.75 g of the sol solution E to obtain a coating liquid for forming a low refractive index layer.

[0049] [Preparation Example 2] Preparation of adhesive layer A four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a cooler was charged with 92 parts by mass of butyl acrylate, 5 parts by mass of N-acryloylmorpholine, 2.9 parts by mass of acrylic acid, 0.1 parts by mass of 2-hydroxybutyl acrylate, and 0.1 parts by mass of 2,2'-azobisisobutyronitrile as a polymerization initiator, together with 100 parts by mass of ethyl acetate. Nitrogen gas was then introduced with gentle stirring to replace the atmosphere with nitrogen, and the polymerization reaction was carried out for 8 hours while maintaining the liquid temperature in the flask at around 55°C, to prepare an acrylic polymer solution. An acrylic adhesive solution was prepared by mixing 0.2 parts by mass of an isocyanate crosslinking agent (Coronate L manufactured by Nippon Polyurethane Industry Co., Ltd., an adduct of trimethylolpropane and tolylene diisocyanate), 0.3 parts by mass of benzoyl peroxide (Niper BMT manufactured by Nippon Oil & Fats Co., Ltd.), and 0.2 parts by mass of γ-glycidoxypropyl methoxysilane (KBM-403 manufactured by Shin-Etsu Chemical Co., Ltd.) with respect to 100 parts by solid content of the obtained acrylic polymer solution. Next, the acrylic adhesive solution was applied to one side of a silicone-treated polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical Polyester Film Co., Ltd., thickness: 38 μm), and dried at 150 ° C for 3 minutes to form an adhesive layer having a thickness of 10 μm. The shear storage modulus G' of the adhesive layer at 60 ° C is shown in Table 1.

[0050] [Preparation Example 3] Preparation of adhesive layer An adhesive layer was obtained in the same manner as in Preparation Example 2, except that the thickness of the adhesive layer was changed to 20 μm.

[0051] [Preparation Example 4] Preparation of adhesive layer An adhesive layer was obtained in the same manner as in Preparation Example 2, except that the thickness of the adhesive layer was changed to 5 μm.

[0052] [Preparation Example 5] Preparation of adhesive layer In a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a cooler, 100 parts by mass of butyl acrylate, 5 parts by mass of acrylic acid, 0.1 parts by mass of 4-hydroxybutyl acrylate, and 0.1 parts by mass of 2,2'-azobisisobutyronitrile as a polymerization initiator were charged together with 100 parts by mass of ethyl acetate, and nitrogen gas was introduced to replace the nitrogen gas while gently stirring, and then the liquid temperature in the flask was kept at around 55°C and a polymerization reaction was carried out for 8 hours to prepare an acrylic polymer solution. 0.6 parts by mass of an isocyanate crosslinking agent (Takenate D101E, trimethylolpropane tolylene diisocyanate, manufactured by Mitsui Chemicals, Inc.), 0.2 parts by mass of benzoyl peroxide (Niper BMT, manufactured by Nippon Oil & Fats Co., Ltd.), and 0.2 parts by mass of γ-glycidoxypropyl methoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd.: KBM-403) were mixed with 100 parts by mass of the solid content of the obtained acrylic polymer solution to prepare a solution of an acrylic adhesive composition. Next, the solution of the acrylic adhesive composition was applied to one side of a polyethylene terephthalate film (Mitsubishi Chemical Polyester Film Corporation, MRF38) that had been treated with a silicone release agent, and dried at 150°C for 3 minutes to form an adhesive layer with a thickness of 15 μm.

[0053] [Preparation Example 6] Preparation of adhesive layer A transparent adhesive sheet (manufactured by Nitto Denko Corporation, LUCIAS (registered trademark), CS986) having a thickness of 25 μm was prepared as an adhesive layer.

[0054] [Preparation Example 7] Preparation of adhesive layer A transparent adhesive sheet (manufactured by Nitto Denko Corporation, LUCIAS (registered trademark), CS986) having a thickness of 50 μm was prepared as an adhesive layer.

[0055] [Examples 1 to 4 and Comparative Examples 1 and 2] The coating liquid for forming the low refractive index layer of Preparation Example 1 was applied onto an acrylic resin substrate (resin substrate, manufactured by Toyo Kohan Co., Ltd.) having a thickness of 30 μm, and the coating film was then dried. In this way, a low refractive index layer was formed on the acrylic resin substrate. The refractive index of the low refractive index layer was 1.19. The thickness of the low refractive index layer was 1.0 μm. Next, the pressure-sensitive adhesive layer obtained in each preparation example shown in Table 1 was transferred onto the surface of the acrylic resin substrate opposite the low refractive index layer. In this manner, a laminate having a structure of low refractive index layer / resin substrate / pressure-sensitive adhesive layer was obtained.

[0056] [Table 1]

[0057] As is clear from Table 1, if the laminate satisfies the above formula (1), it will have excellent adhesion to the object to be attached even in a high humidity environment, and will have an excellent appearance with no visible waviness of the adhesive. [Industrial Applicability]

[0058] The laminate according to the embodiment of the present invention can be used in various optical products, and can be particularly suitably used in optical products including a light guide plate. [Explanation of symbols]

[0059] 1 Resin substrate 2. Low refractive index layer 3 Adhesive layer 100 Laminate

Claims

1. A resin substrate; a low refractive index layer having a refractive index of 1.30 or less, the low refractive index layer being disposed on one side of the resin substrate; a pressure-sensitive adhesive layer disposed on the opposite side of the resin substrate to the low refractive index layer, A laminate satisfying the following formula (1), where G' is the shear storage modulus of the pressure-sensitive adhesive layer at 60° C. and t is the thickness of the pressure-sensitive adhesive layer: 2000 [Pa / μm]≦G' / t≦15000 [Pa / μm]...(1)

2. The laminate according to claim 1 , wherein the thickness t of the pressure-sensitive adhesive layer is greater than 5 μm and less than 50 μm.

3. The laminate according to claim 1 or 2, wherein the pressure-sensitive adhesive layer has a shear storage modulus G' of 80,000 Pa or more at 60°C.

Citation Information

Patent Citations

  • Variable index light extraction layer and method of making the same

    WO2014031726A1